Metabolic shifts of oceans: Summoning bacterial interactions. (May 2022) - Galbraith, Elroy; Frade, P.R.; Convertino, Matteo
Graphical abstract: Highlights: Variations in allometric scaling relationships can signal ecosystem stress. Bacterioplankton interactions scales with abundance by 2/3-power. Community organization explains variations better than biogeochemical organization. Keystone phyla have many weak but salient interactions despite rarity. Habit architecture modulates biogeochemical pressure on community metabolism. Abstract: Metabolic scaling can pinpoint monitoring priorities for anomalous communities and inform local eco-engineering restoration enhancing ecosystem function. We discovered an entropic Kleiber's Law between bacterioplankton phylum total directed interactions and population and community abundane, with an average exponent Φ ≃ 2 3 in striking accordance with theoretical expectations. The taxa-independent allometric relationship largely varies by habitat (shifting from 2/3 to 3/4 as power-exponent) and is better explained by the community abundance spectrum and its organization than by the envirome defined by environmental interactions. Yet, greater envirome disorganization meant higher environmental impacts causing larger bacteriome disorganization toward random interaction topologies and higher Kleiber's Law exponents. Habitat-related bacteriome differences revealed that keystone phyla were highly interacting and rare (like Acidobacteria, SBR1093, and ZB3) maintaining weak but salient interactions with both rare (like Spirochaetes and Firmicutes) and dominant phyla. Consistent with their small divergence from main Kleiber's law and abundance spectrum patterns cosmopolitan phyla, like Bacteroidetes and Proteobacteria, were dominant but weakly interacting (in magnitude) emphasizing the importance of weak ties in collective dynamics. The most salient interactions were always between phyla with high and low node centrality defined by their total directed interactions and abundance. Envirome network centrality shows temperature and nutrient concentrations (total and dissolved organic phosphorus) as central in estuarine habitats impacted by both global ocean factors and near-shore river effluxes; salinity and suspended particle matter were central in more off-shore habitats. Our results emphasize the importance of a probabilistic assessment of community interactions over individual bacterial abundance analyses when searching for collective patterns informative of ecosystem state and their environmental determinants.